The Influence of Competency and Compensation on Employee Performance at PT. Berkah Bersama Gemilang Outlet Hertasning Branch - Andardinata, Ady; Alimuddin, Muhammad Ilham; Pratiwi, Ayu (Perpustakaan dan Penerbitan Unismuh Makassar, 2023)
This research aims to analyze the influence of competency and compensation on employee performance at PT. Berkah Bersama Gemilang Outlet Hertasning Branch. The research method uses qualitative and quantitative data, with descriptive analysis and multiple linear regression. The research results show that competency and compensation have a positive and significant influence on employee performance in the branch. Competency, as a combination of knowledge, skills and attitudes, helps improve employee performance. Fair and appropriate compensation, including salary and bonuses, also has a positive impact on performance.Through regression testing, it was found that competence and compensation together contributed positively to employee performance. Statistical analysis shows that the coefficient of determination reaches 80.6%, indicating that competence and compensation explain variations in employee performance of that magnitude. The F test also shows the joint significance of the two independent variables on the dependent variable.These findings are in line with related theories, supporting the view that increasing competence and providing fair compensation can increase employee morale. Therefore, companies are advised to continue to improve employee competency and ensure a compensation system that is transparent and in line with performance contributions. This research contributes to the understanding of the factors that influence employee performance in certain industries, as well as providing a basis for the development of more effective human resource management policies.